Pengaruh Metode PQRST dalam Pembelajaran Keterampilan Membaca Teks Deskripsi Siswa Kelas VII SMP Negeri 3 Kota Sungai Penuh - Aprilia, Aprilia; Afnita, Afnita (MASALIQ, 2023)
This study aims to see the effect of the PQRST method in learning the skills of reading descriptive texts for class VII students of SMP Negeri 3 Kota Sungai Lilin. The type of research used in this research is quantitative research with a quasi-experimental method using a one group pretest-posttest design. The population in this study were 105 class VII students of SMP Negeri 3 Kota Sungai Kunci for the academic year 2022/2023, with a sample size of 26 students who were determined using a purposive sampling technique. Based on the results of the posttest and hypothesis testing, it was found that the average value of skills in reading descriptive texts after using the PQRST method was higher than the average value of skills in reading descriptive texts before using the PQRST method. learning the skills of reading descriptive text after using the PQRST method is in the Very Good (BS) classification with an average value of 96.15. When compared with the learning value of reading skill description text for class VII students of SMP Negeri 3 Kota Sungai Lilin before using the PQRST method it is lower and is in the Less Enough (KC) classification with an average value of 15.38. Based on the t-test it was concluded that the hypothesis (H1) was accepted at a significant level of 95% and dk = (n-1) because tcount > ttable (20.26>1.70). Thus, it can be concluded that there is an effect of the use of the PQRST method on the skills of reading descriptive texts for class VII students of SMP Negeri 3 Kota Sungai Lilin.